Ejecución presupuestal y su relación con el crecimiento económico del distrito de Tarapoto en el periodo 2008-2013 - Castañeda Ocampo, Carlos Alberto (2014)
This research entitled "BUDGET EXECUTION AND ITS RELATIONSHIP WITH GROWTH DISTRICT IN THE PERIOD 2008-2013 TARAPOTO" this research is to evaluate the overall budget execution by the district municipality of Tarapoto and establish its relationship with the economic growth in the period of study, taking as hypothesis the existence of a direct link between budget execution and economic growth in the period under study, then to determine the budget execution, the population consisted of all residents of the district of Tarapoto to date total 68.295 inhabitants, taking as example to 90 residents of the city of Tarapoto, which then proceeded to survey the study sample and gather information from economic growth during the period of study and have obtained the following other results: it can be seen that the achievement of goals of the City of Tarapoto been developing a regular basis, and that 44% of respondents named it as poor, 44% as fair and 12% as efficient. It can be seen that the budget implementation develops poorly with trends regularly (46% poor, 41% fair, 13% efficient). We can determine that there is perhaps an economic growth in our city, but not roughly, as compared to production in agriculture has achieved a total of S /. 1 543.456 in 2008 (start of the study period) , so I had a growth of S /. 2 234.678 by 2013 (end of the study period). Having tabulated and analyzed the results obtained in this investigation, its conclusions states that: In terms of budget execution takes place on a regular basis, since there has been full compliance with budgeted projects come as no programming appropriate goals and budget execution itself develops badly, since the respective guidelines for the effective execution of investments is not followed. As for the economic growth of the district of Tarapoto, it has been determined an increase in the period of study, but not roughly, and this period of five (5) years